Indonesian and English Lexical Metaphoric Expressions Used In Online Competition News Text - Siti Tarwiyah (IAIN Salatiga, 2016)
The subject of this article deals with discourse semantics. The focus of its description is metaphoric expressions used to express competition news in online media. Based on some theories about metaphor, the writer tries to search for kinds of metaphoric expressions used and the reasons behind the use of the expressions. The result shows that English and Indonesian language use lexical metaphors with three specifications, i.e. anthropomorphic, animal, and synesthetic. The choice of specific lexical metaphoric expressions is related to situational and cultural aspects.